Serum interleukin-2 and neopterin levels as useful markers for treatment of active pulmonary tuberculosis - Turgut, Teyfik; Akbulut, Handan; Deveci, Figen; Kacar, Canan; Muz, M. Hamdi (Tohoku Univ Medical Press, 2006)
TURGUT, T., AKBULUT, H., DEVECI, F., KACAR, C. and Muz, M.H. Serum Interleukin-2 and Neopterin Levels as Useful Markers for Treatment of Active Pulmonary Tuberculosis. Tohoku J. Exp. Med., 2006, 209 (4), 321-328 - Macrophages and T cells are responsible for the main immune response to tuberculosis by secreting many cytokines and other substances. The aim of this study was to determine the effects of multidrug treatment on serum levels of interleukin-2 (IL-2), secreted by activated T cells, and of neopterin, secreted by macrophages and monocytes, in patients with pulmonary tuberculosis. The study included 30 patients with active pulmonary tuberculosis, confirmed by the detection of acid-fast bacilli in direct sputum smears and/or sputum cultures. The serum levels of IL-2 and neopterin were measured before and during the treatment and compared with 15 patients with inactive pulmonary tuberculosis and 15 healthy controls. Serum IL-2 and neopterin levels were higher in patients with active tuberculosis (164.53 +/- 58.91 pg/ml and 69.54 +/- 29.42 nmol/l, respectively) than those in inactive tuberculosis (95.43 +/- 31.17 pg/ ml and 10.71 +/- 1.78 nmol/l) or controls (79.20 +/- 14.81 pg/ml and 9.50 +/- 2.27 nmol/l) (p < 0.001 for each parameter). No significant differences were found in IL-2 and neopterin levels between inactive tuberculosis and control subjects. The IL-2 levels remained elevated in active tuberculosis at 2nd month of treatment (p < 0.001) and decreased to the control levels after 4th month. Neopterin levels were significantly higher in active tuberculosis than those in inactive tuberculosis or controls at the 2nd and 4th months of treatment. These findings indicate that measurements of serum IL-2 and neopterin levels are useful in following up the treatment and immune response to tuberculosis. - Pulmonary tuberculosis; interleukin-2; neopterin (c) 2006 Tohoku University Medical Press.
Keywords: Cell-Mediated-Immunity; Responses; Activation